An Unusual Case of Progressive Myoclonic Epilepsy (PME): Familial Encephalopathy with Neuroserpin Inclusion Body (FENIB) - Das, Debarup; Chakraborty, Uddalak; Dubey, Souvik; Bhattacharya, Bhaswar; Pandit, Alak (Journal of Pediatric Epilepsy, 2023)
Progressive myoclonic epilepsy (PME) is a spectrum with epileptic encephalopathy and myoclonus. In this case report authors describe a young patient presenting with refractory multifocal myoclonus with multiple seizure types with dyscognitive features. He was bed-bound with complete dependency on his caregivers. His electroencephalogram had an encephalopathy pattern, and his magnetic resonance imaging showed gross cortical atrophy. In this patient, the working clinical diagnosis of epileptic encephalopathy with PME phenotype had a wide differential list including neuronal ceroid lipofuscinosis, Lafora body disease, sialidosis, myoclonic epilepsy with ragged red fibers, dentatorubro-pallidoluysian atrophy, Unverricht–Lundborg, and other rare disorders such as Gaucher's disease and other genetic causes. Eventually after ruling out all common etiologies, whole-exome sequencing revealed a SERPINI1 gene mutation in exon 9 showing a pathogenic variant c1175G > A (p.Gly392Glu) which associated with PME as a part of familial encephalopathy with neuroserpin inclusion bodies.
Keywords: myoclonic epilepsy; neuroserpin; encephalopathy